Teaching online with an artificial pedagogical agent as a teacher and visual avatars for self-other representation of the learners. Effects on the learning performance and the perception and satisfaction of the learners with online learning: previous and new findings - Herbert, Cornelia; Dołżycka, Joanna Daria (Frontiers in Education, 2024)
Building upon previous research, this study aims to provide answers to the questions of how the presence a humanoid artificial pedagogical agent as teacher and instructor and visual self-other representation of the learners through avatars influence the immediate cognitive performance and learning experience in online learning among adult learners. Several outcome measures were investigated to evaluate if effects are the same or different for the different experimental conditions and if learning with the pedagogical agent and visual self-other representation is modulated by the learner’s previous experiences with and preferences for online learning. Teacher presence and self-other presence of the learners were experimentally manipulated. A humanoid artificial agent, visible on all of the slides of the online course material and instructing the material represented the teacher. The avatars of the learners (self-avatar and peer avatars) were kept of minimal functionality but self-avatars were preselected or could be self-selected by the learners. The learner’s cognitive learning performance, the learner’s attention to the pedagogical agent, their sense of teacher presence and of self- and other-presence, their satisfaction with the course as well as the learner’s previous learning experiences were measured by cognitive testing, self-report, and linguistic analysis as major performance indicators and a positive learning experience. The analysis comprised 133 university students and results were additionally compared for two subsamples. Learning performance, learning satisfaction, and the degree of attention to the teacher were positively related. In addition, positive evaluations of the cognitive presence elicited by the teacher were found. Self- or other-presence of avatars did not significantly influence the learner’s performance beyond teacher presence but the learner’s perception of it and their motivation to study online. The study and its results extend the previous literature that focused on the effects of pedagogical agents in online teaching or on virtual representations of the learner's self and classmates in online learning. Despite limitations, the results of this study provide insights into combining teaching with artificial pedagogical agents and visual avatars for self-other representation during online teaching and the observations can serve as catalyst for future research.